Peningkatan Kompetensi Guru dalam Pembuatan Media Pembelajaran Canva Melalui Bimbingan dan Pelatihan Berbasis Kemandirian Di SMK Negeri 1 Tanjungpinang Tahun Pelajaran 2021/2022 - Delisbeth Delisbeth (Ridwan Institute, 2022)
This research was conducted to determine the improvement of teacher competence through guidance and training on the application of Canva learning media. The method used in this research is school action research which consists of 2 cycles, each cycle consists of planning, action, observation and reflection. The data collection procedure was carried out by presenting Canva learning media collection in the form of animation. The process of guidance and training is carried out with peer tutors. The results of the study on improving teacher competence in making Canva learning media through Guidance and Training for teachers at SMK Negeri 1 Tanjungpinang obtained 60% results in the first cycle and 90% in the second cycle. From the results of the two cycles the increase was 30%. So it can be said that Guidance and Training can improve teacher competence in using Canva media.